Phylogenetic Analysis of Scaphoideus Reveals New Insights Into the Invasion History of Scaphoideus titanus (Hemiptera, Cicadellidae) in Europe - Juan Sebastian Enciso Garcia; Erika Corretto; Lapo Ragionieri; Luciano Palmieri; Edel Peréz‐López; Christopher Dietrich; Eric Lombaert; Katrin Janik; Hannes Schuler (Ecology and Evolution)
ABSTRACT The genus Scaphoideus is one of the most diverse groups in Deltocephalinae with significant pest species, including the American grapevine leafhopper Scaphoideus titanus Ball, the vector of Flavescence dorée phytoplasma in European grapevines. Despite the diversity and the agricultural importance of these species, limited information regarding the phylogenetic relationships of Scaphoideus species is available. Furthermore, although S. titanus is one of the most important pest of grapevine in Europe, details on its intraspecific genetic variation are limited to only a few studies based on single mitochondrial markers. By sequencing the complete mitochondrial genomes of S. incisus Osborn, S. melanotus Osborn, S. minor Osborn, S. nigrisignus Li, and S. titanus, we examined the phylogenetic relationships among these species. We specifically investigated the genetic differences between S. titanus populations from North America and Europe to reveal new insights on the invasion history of this species in Europe. Based on our dataset, two distinct genetic clades of S. titanus with more than 10% pairwise genetic distance were identified in the native range: one comprising Midwestern USA and Quebec, Canada and a second one with individuals from Ontario, Canada. Morphological analysis of the aedeagus showed differences between the two clades, suggesting that they should be considered as different species. Invasive European populations share high mitochondrial similarity with those from Ontario, supporting the hypothesis that the invasion originated from this region. Our data reveal new insights into the invasion history of this important pest species and highlight the need for a taxonomic revision of the S. titanus species complex.